Hospital based cancer registry in Cipto Mangunkusumo hospital Jakarta (Medical Journal of Indonesia, 2000)
Registrasi kanker berbasis rumah sakit di RSUPN Cipto Mangunkusumo, Fakultas Kedokteran Universitas Indonesia, telah dimu/ai tahun 1997, bertujuan untuk memberi data bagi program pengendalian kanker dan membanlu perencanaan rumah sakit. Maka/ah ini menyajikan registrasi kanker sepanjang tahun 1997-1998. Data dari semua pasien kanker yang baru terdiagnosis dicatat pada Formulir Registrasi Kanker. Yang didata ialah identitas pasien, demografi dan kultur, penilaian tumor dan usia, serta penatalaksanaan. Terdapat 2144 (0.48%) penderita kanker diantara 444.178 pasien baru yang berobat ke RSCM. Perbandingan perempuan dan laki-laki ada/ah 1.7 : 1. Usia terbanyak pada perempuan ada/ah 35-44 tahun, pada /aki-laki 45-54 tahun. Usia rata rata saat terdiagnosis umumnya lebih muda dibanding senter lainnya. Pada perempuan, kanker terbanyak ada/ah lqmker serviks, disusul o/eh payudara dan nasofaring sedang pada /aki-/aki terbanyak nasofaring, sumsum tu/ang dan hati. Pada anak, terbanyak ada/ah leukemia limfositik akut, leukemia non limfositik akut, retinob/astoma dan nefroblastoma . Pendidikan penderita perempuan lebih rendah dibanding laki-laki . Perempuan penderita kanker serviks. kulit, sumsum tu/ang, kelenjar getah bening dan laki-laki penderita kanker sumsum tulang, kelenjar getah bening dan mata mempunyai pendidikan yang lebih rendah. Sebanyak 85% diagnosis ditegakkan secara mikroskopik. Jum/ah kanker stadium awa/ lebih rendah dibanding stadium /anjut (47% vs 53%). Pada tahun 1998 terapi awal yang paling banyak diberikan ada/ah berturut-turut radioterapi, bedah dan kemoterapi. Hanya 45% pasien yang mempero/eh terapi da/am 3 bu/an pertama sete/ah diagnosis. Abstract The Hospital Based Cancer Registry in Registry in Cipto Mangunkusumo National Center General Hospital (RSCM), the teaching hospital of the Faculty of Medicine University of Indonesia, was set up in 1997. Its aims were toprovide information on the magnitude of cartcer problems , and data for focussing cancer control programs, to facilitate thefollow up and to help plan hospital facilities . This paper presents a summary of the cancer registry data collected during the period of 1997-1998. Data from al newly diagnosed cancer patients was recorded in Cancer Registration Forms by the oncology doctors. The collected items of information were patient 's identification, demographic and cultural items, the tumor and its investigations, and the treatment. There were 2144 (0.48%) cancer patients among 444,178 new patients treated in RSCM hospital. The female to male patients ratio was 1.7 : 1. The age peak ed in females within 35-44 years, and in males within 45-54 years. In general. the mean age at diagnosis of various cancer was younger compared to other centers. In females, the most common cancers were cervical, breast, and nasophayngeal, and in males, they were nasopharyngeal, bone marrow, and liver cancers. In children, the most common cancers were acute lymphocytic leukemia, acute non lymphocytic leukemia, acute non-/ymphocytic leukemia, retinoblastoma, and nephrob/astoma . Female patients had lower educational level than males. Females with cervical, skin, bone marrow, lymph nodes cancer and males with bone marrow, lymph nodes and eye malignancy had lower educational level. There were 85% patients diagnosed by microscopic examination. The number of early stage cancer was lower corned to late stage cases (47% vs 53%). In 1998, the most frequent initial treatment was radiotherapy, followed by surgery and chemotherapy, and only 45% patients received treatments within 3 months after diagnosis. Keywords: Cancer registry, site, age, education, staging, diagnosis, treatment